1972
DOI: 10.1128/jvi.10.1.42-50.1972
|View full text |Cite
|
Sign up to set email alerts
|

Specific Fragments of φX174 Deoxyribonucleic Acid Produced by a Restriction Enzyme from Haemophilus aegyptius , Endonuclease Z

Abstract: A restriction-like enzyme has been purified from Haemophilus aegyptius. This nuclease, endonuclease Z, produces a rapid decrease in the viscosity of native calf thymus and H. influenzae deoxyribonucleic acids (DNA), but does not degrade homologous DNA. The specificity of endonuclease Z is different from that of the similar endonuclease isolated from H. influenzae (endonuclease R). The purified enzyme cleaves the double-stranded replicative form DNA of bacteriophage 4X174 (+X174 RF DNA) into at least 11 specifi… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1

Citation Types

0
37
0

Year Published

1974
1974
2002
2002

Publication Types

Select...
7
2

Relationship

0
9

Authors

Journals

citations
Cited by 205 publications
(37 citation statements)
references
References 16 publications
0
37
0
Order By: Relevance
“…The next important step was taken when these experiments were repeated using a different restriction enzyme, endonuclease Z, to produce another set of DNA fragments, some of which overlapped the first set (240). At least 11 fragments with molecular weights differing from those produced by endonuclease R were separated.…”
Section: Biological Activity Of Dna Fragmentsmentioning
confidence: 99%
“…The next important step was taken when these experiments were repeated using a different restriction enzyme, endonuclease Z, to produce another set of DNA fragments, some of which overlapped the first set (240). At least 11 fragments with molecular weights differing from those produced by endonuclease R were separated.…”
Section: Biological Activity Of Dna Fragmentsmentioning
confidence: 99%
“…The DNA sequencing results con¢rm the restriction cleavage analysis and strongly suggest that the B. anthracis restriction enzyme is an isoschizomer of HaeIII. The RE HaeIII was ¢rst described in 1972 [25]. The ¢rst communication of an isoschizomer of HaeIII from Bacillus genus (subtilis) named Bsu1076I was described 4 years later [26].…”
Section: Resultsmentioning
confidence: 99%
“…The profiles of digestion products of pBR322, pUC9 and lDNA with SbuI indicated that SbuI might be an isoschizomer of HaeIII from Haemophilus aegypticus (Middleton et al 1972) with a recognition sequence 5'-GGCC-3'. A double digest of SbvI and HaeIII on pBR322 DNA confirmed that these enzymes were isoschizomers ( Fig.…”
Section: Resultsmentioning
confidence: 99%